Heterogeneous Antibiotic Resistance Gene Removal Impedes Evaluation of Constructed Wetlands for Effective Greywater Treatment - Daniella Itzhari; Weitao Shuai; Erica M. Hartmann; Zeev Ronen (MDPI AG, 2024)
Microorganisms carrying antimicrobial resistance genes are often found in greywater. As the reuse of greywater becomes increasingly needed, it is imperative to determine how greywater treatment impacts antimicrobial resistance genes (ARGs). Using qPCR and SmartChip™ qPCR, we characterized ARG patterns in greywater microbial communities before, during, and after treatment by a recirculating vertical flow constructed wetland. In parallel, we examined the impact of greywater-treated irrigation on soil, including the occurrence of emerging micropollutants and the taxonomic and ARG compositions of microbial communities. Most ARGs in raw greywater are removed efficiently during the winter season, while some ARGs in the effluents increase in summer. SmartChip™ qPCR revealed the presence of ARGs, such as tetracycline and beta-lactam resistance genes, in both raw and treated greywater, but most abundantly in the filter bed. It also showed that aminoglycoside and vancomycin gene abundances significantly increased after treatment. In the irrigated soil, the type of water (potable or treated greywater) had no specific impact on the total bacterial abundance (16S rRNA gene). No overlapping ARGs were found between treated greywater and greywater-irrigated soil. This study indicates ARG abundance and richness increased after treatment, possibly due to the concentration effects of the filter beds.